106
Asish Mahapatra
·2010-08-17 08:26:04
consider g(x) = f2(x) - x2
g(a) = g(b) (given)
=> there exists some c belongs to [a,b] st
g'(c) = 0 (by rolle's theorem)
=> 2f(c).f'(c) - 2c = 0
=> f(c)*f'(c) = c
hence proved
thx for the question .. going to be useful for my midsems
1
bindaas
·2010-08-18 00:16:53
well i had cauchy's mean value theorem in my mind
i chose
h(x)=f^2(x) \ and\\ g(x)=x^2
by cauchy MVT
\frac{h'(c)}{g'(c)}=\frac{f^2(b)-f^2(a)}{b^2-a^2} \\ \frac{2f(c)f'(c)}{2c}=1 \\ f(c)f'(c)=c \\ \texttt{for some c}\in[a,b]
1
bindaas
·2010-08-18 00:21:24
another one for asish
a simpler one this time
\boxed{Q1}
\texttt{let f and g be continous , real valued functions satisfying the following conditions} \\ \texttt{i)f and g are continous in [a,b]}\\ \texttt{ii)f and g are differntiable in (a,b)}\\ \texttt{iii)f(a)=f(b)=0} \\ \texttt{then shoe that for some c } \in [a,b]\\ f(c)g'(c)+f(c)=0
\boxed{Q2}
\texttt{let f be a continous and differntiable function f(0)=0 and f'(0)=1 }\\ \texttt{then prove that } \\ \lim_{x\rightarrow \infty}\frac{1}{x}\left(f(x)+f(\frac{x}{2})+f(\frac{x}{3})\cdots+f(\frac{x}{k}) \right)=1+\frac{1}{2}+\frac{1}{3}+\cdots+\frac{1}{k}
Q2 my doubt
1
bindaas
·2010-08-18 00:23:37
i request nishant sir to make a separate sub forum for us engineering students , as we need some interface to communicate and share our ideas
23
qwerty
·2010-08-18 02:41:41
bindaas i think for 2nd one lim shud be x -> 0 ,
u can see it by L'Hospital
or since f(0)= 0, \lim_{x\rightarrow 0}\frac{f(\frac{x}{r})-f(0)}{x}=\frac{f^{!}(\frac{x}{r})}{r}=\frac{1}{r}
so \lim_{x\rightarrow 0}\sum{\frac{f(\frac{x}{r})}{x}}=\sum{\frac{1}{r}}
for 1st one u made some typing error ?
106
Asish Mahapatra
·2010-08-18 05:37:34
Q2. isnt it x--> 0 instead of x--> inf,
we have similar question in our assignment but with x-->0 and the method is obviously LH rule
Q1 probably a typo in it... pl check the question
1
bindaas
·2010-08-18 23:44:01
qwerty's argument seems fine
Q1 is having a minor error which i think u guys cud have made out
\texttt{let f and g be continous , real valued functions satisfying the following conditions} \\ \texttt{i)f and g are continous in [a,b]}\\ \texttt{ii)f and g are differntiable in (a,b)}\\ \texttt{iii)f(a)=f(b)=0} \\ \texttt{then shoe that for some c } \in [a,b]\\ f(c)g'(c)+f'(c)=0
66
kaymant
·2010-08-19 05:55:17
For the above question set
h(x) = f(x) eg(x)
and the result follows from Rolle's theorem on h(x) in [a,b]. And by the way, c should be in the open interval (a,b) and not the closed one.
1
bindaas
·2010-08-19 06:48:53
needless to say kaymant sir is always right :)
wanted some juniors participation in it
106
Asish Mahapatra
·2010-08-19 07:13:54
yeah but how do we think abt that ..
needless to say this has been discussed in our tutorials...
1
bindaas
·2010-08-20 05:30:30
the basic idea is very easy
try solving for g(c)
g'(c)=-\frac{f'(c)}{f(c)}
the term \frac{f'(c)}{f(c)}
says something to do with ln or e^
then its not tough to square onto that function